Meningkatkan Kontribusi Penyuluhan Agama Islam dalam Pemberantasan Korupsi - ., Syuhada (UIN Antasari Banjarmasin, 2012)
Under Indonesian law there are 30 types of corruption. For eradication, the government has made a variety of rules and institutions, including the Corruption Eradication Commission (KPK), but corruption remains a problem that must be dealt with in Indonesia. Ministry of Religion as an institution that serves to foster religious life has made various efforts to make ummah obedient to Islamic teachings, religious and morally commendable. One of its efforts is to provide Islamic counseling. However, counseling still should be increased in order to contribute to corruption eradication. The contribution can be made by encouraging the extension of Islamic counseling through the development of curriculum and materials used to be consulted with the addition of an understanding of the thirty kinds of corruption, Islamic moral teachings and principles violated by the perpetrators of corruption